Generalized Ordinary Differential Equations : Not Absolutely Continuous Solutions. - Kurzweil, Jaroslav (Singapore : World Scientific, 2012)
This book provides a systematic treatment of the Volterra integral equation by means of a modern integration theory which extends considerably the field of differential equations. It contains many new concepts and results in the framework of a unifying theory. In particular, this new approach is suitable in situations where fast oscillations occur.
24. A convergence process as a source of discontinuities in the theory of differential equations25. A class of Strong Riemann-integrable functions; 26. On equality of two integrals; 27. A class of Generalized ordinary differential equations with a restricted right hand side; Appendix A. Some elementary results; Appendix B. Trifles from functional analysis; Bibliography; Symbols; Subject index.
Print version record.
Includes bibliographical references (pages 193-194) and index.
eBooks on EBSCOhost
Keywords: Differential equations; Integral equations; Équations différentielles.; Équations intégrales.; MATHEMATICS -- Differential Equations -- Ordinary; Differential equations; Integral equations